The 5-UPTM protocol for unified multiservice wirelessnetworks. - McFarland, B. (IEEE Communications magazine)
Popular wireless networking protocols such as Bluetooth, IEEE 802.11, and HomeRF were originally developed for the 2.4 GHz frequency band by organizations that made design tradeoffs based on values such as complexity, price, and performance. Because the protocols were developed independently and these values differed according to the markets and applications the organizations intended to serve, the various protocols do not easily interoperate with one another and can cause significant mutual interference in the same radio space. The problem becomes especially acute in environments such as residential networks where a single network may be required to serve a broad range of application classes. A newer high-performance wireless LAN standard, IEEE 802.11a, operates in the 5 GHz band and offers much higher speeds than previous WLAN standards, but does not adequately provide for unified networks that support multiple classes of devices with differing speed, performance, power, complexity, and cost requirements. These differing classes of devices will become increasingly important as LANs move beyond the limits of office-oriented computer interconnection services and into the realm of data, video, and audio distribution services for interconnected devices in offices and homes. The 5 GHz unified protocol (5-UPTM) is a proposed extension to existing 5 GHz wireless LAN (WLAN) standards that supports data transfer rates to over 54 Mb/s and also allows a wide variety of lower-power lower-speed devices carrying diverse traffic types to coexist and interoperate within the same unified wireless network